Empowering Teachers: AI Tools for Enhancing English Education in Pontianak Urban Schools - Ningsih, Ratih Sulistiya; Sudharni, Sudharni; Yuliana, Yohanes Gatot Sutapa; Riyanti, Dwi (Journal of English Education Program, 2025)
This research is a qualitative descriptive study of English language educators' views and practices regarding the integration of artificial intelligence (AI) tools in education. It aims to understand how teachers in Pontianak Urban Schools perceive the effectiveness of AI tools in enhancing their English teaching practices, what challenges teachers face in integrating AI tools into English language teaching, and how the use of AI tools affects student engagement and motivation in learning  English. The participants were two English language teachers from an urban school in Pontianak, West Kalimantan. Data were gathered through semi-structured interviews, with thematic analysis used for data interpretation. The results show that both teachers used AI to help them in the teaching process. They also expressed the need for more training and support to effectively integrate the AI tools. The study offers insights into teachers"™ perceptions of AI in education and highlights the importance of responsible AI integration in language teaching.